Re-institute website - and RE!NSTITUTE (2023)
We are a dynamic non-profit organization with a unique approach to managing change and catalyzing innovation to support global systems transformation. We know that to achieve equal, just, and safe communities, we must collectively challenge and change the systems that people rely on — especially those most vulnerable. Together, we must RE!BUILD a system's resilience and capacity to take on our biggest generational challenges. Justice, housing, health, and other systems in every country are often struggling to come together, across institutions and organizations, to unite under a common vision for change, and implement those changes in effective and innovative ways. Our work and methodology — the 100-Day Challenge — are designed to support these systems to achieve extraordinary results. Our approach is rooted in the philosophy that frontline staff, supported by leadership, can unleash innovation and achieve incredible results by creating new relationships, experimenting with fresh ideas from across their system, and building authentic engagement with those with lived experience.